Pengaruh Stres Kerja dan Beban Kerja Terhadap Kinerja Karyawan dengan Faktor Usia sebagai Variabel Moderating di PD. Pido Busana - Pipit Siti Nuraisyah; Ida Jalilah Fitria (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to explore the relationship between work stress, workload and employee performance, by considering the age factor as a moderating variable. The research method used was a survey using a questionnaire distributed to employees from various age backgrounds in the industrial sector. The collected data was analyzed using multiple regression analysis to determine the influence of the independent variable on the dependent variable, as well as to test the presence of the moderating effect of the age factor. The research results show that work stress and workload have a significant influence on employee performance. In addition, moderating analysis revealed that the age factor influenced the strength and direction of the relationship between job stress, workload, and employee performance.